Muscle-building interventions improve glucose metabolism in elderly type 2 diabetic patients with sarcopenic obesity - Tingting Han; Xinyue Liang; Hongxia Liu; Mingyu Zhu; Sisi Shen; Jia Song; Hongwei Chen; Ningxin Chen; Yue Liu; Ziyi Wei; Yurong Weng; Xian Jin; et al. (Nutrition & Metabolism)
Abstract Background Among all the elderly patients with type 2 diabetes mellitus (T2DM) of different body compositions, patients with sarcopenic obesity exhibited the most severe degree of insulin resistance despite possessing a normal body weight. It is well-established that interventions encompassing resistance training alone or in combination with whey protein supplementation, referred to hereafter as muscle-building interventions, are effective for increasing muscle mass and function in the elderly population. However, the impact of these muscle-building interventions on glucose metabolism in elderly T2DM patients with sarcopenic obesity remains unclear. The objective of this study was to elucidate the effect of muscle-building interventions on blood glucose and insulin resistance in elderly T2DM patients with sarcopenic obesity. Methods The muscle-building interventions in this study included resistance training alone and resistance training combined with whey protein supplementation. In this randomized controlled trial, elderly T2DM patients with sarcopenic obesity were divided into three distinct groups: the control group, the resistance training group, and the resistance training combined with whey protein supplement group. The muscle-building interventions were conducted for 12 weeks. Results Implementing muscle-building interventions showed significant improvements in glycemic indices (HbA1c, OGTT 2-hour plasma glucose) and insulin resistance levels (HOMA-IR, Gutt index) for elderly T2DM patients with sarcopenic obesity. These muscle-building interventions enhanced muscle functional indices (handgrip strength, 5-time chair stand test). The combination of resistance training with whey protein supplementation did not significantly enhance the favorable effects on glucose metabolism compared to resistance exercise alone. Correlation analyses revealed that improvements in muscle strength were significantly associated with enhancements in glucose metabolism. Conclusions In elderly T2DM patients with sarcopenic obesity, muscle-building interventions (particularly resistance exercise) have been shown to significantly improve blood glucose control and insulin resistance.